Diseases and conditions associated with obesity and analysis of their treatment effectiveness - M. B. Lyasnikova; M. I. Silkina; N. A. Belyakova; S. S. Rubina (Лечащий Врач)
Background. The relevance of this study is explained not only by the widespread prevalence of obesity in the world, but also by a number of related diseases that lead to decreased ability to work and disability of patients. The article presents data on diseases associated with obesity, characteristics of carbohydrate and fat metabolism, characteristics of obstructive sleep apnea syndrome (OSAS), the results of psychological testing and eating disorders in these patients, and also analyzes the effectiveness of their treatment in an outpatient setting.Materials and methods. For this purpose, 76 patients aged from 30 to 60 years who consulted an endocrinologist due to excess body weight were examined. They were ranked by degree of obesity. The examination was carried out against the background of antihypertensive, hypoglycemic, and antihyperlipidemic therapy. The majority of patients (82%) had degrees II and III obesity, with morbid obesity amounting to 49%. All patients, regardless of the degree of obesity, had abdominal type, arterial hypertension (mainly diastolic), and half of them had hyperglycemia, hypertriglyceridemia, increased levels of very low-density lipoprotein cholesterol and gamma-glutamyl transpeptidase, insulin resistance, depression, which increased with severity obesity.Results. The data obtained indicate the lack of effectiveness of therapy carried out in outpatient settings. Treatment for obesity was carried out in almost half of those examined, but it was a course with the return of body weight after its cessation. However, it is well known that the treatment of obesity is a complex and lengthy process, which necessarily includes a psychotherapeutic approach. Most obese patients are diagnosed with OSAS, but ¼ of patients received treatment for this disorder. Almost all patients with severe obesity had eating disorders.Conclusion. Based on all of the above, the practical significance of our research is determined. So, at an appointment with a doctor for weight correction, testing should be carried out to identify the type of eating disorder and the level of depression, as predictors of weight gain, the development of obesity and related diseases and metabolic disorders. In addition, conduct questionnaires to identify sleep disorders and select patients for polysomnography followed by CPAP therapy.